A Review Of Sharia Economic Law On Cake Pricing: A Study At Elly's Cake Store, Sukarame District, Bandar Lampung City - Aldino Ferdi Elpandha; Iskandar Syukur; Pramudya Wisesha (JURNAL ILMU SYARIAH, 2026)
Pricing is one of the most important aspects of commercial transactions, as it is closely related to the realization of justice, transparency, and a balanced distribution of rights and obligations between sellers and buyers. In practice, ELLY'S Cake Store, located in Sukarame District, Bandar Lampung City, implements a pricing policy that differentiates between returning customers and new customers for the same products. This practice raises questions regarding its conformity with the principles of Sharia Economic Law. This study aims to examine the pricing mechanism implemented at ELLY'S Cake Store, analyze its conformity with the principles of Sharia Economic Law, and propose a general analytical framework for assessing loyalty pricing practices within fiqh al-mu’āmalah. This research employed a qualitative approach using a field research design. Data were collected through observation, in-depth interviews, and documentation involving the store owner, one employee, one returning customer, and one new customer, selected through purposive sampling. The data were analyzed using data reduction, data display, and conclusion-drawing techniques, with source and method triangulation applied to strengthen the trustworthiness of the data. The findings indicate that the pricing mechanism is determined by considering production costs, raw material prices, operational expenses, market conditions, and strategies to maintain customer loyalty. The price differences offered to returning customers are intended as a form of appreciation for their loyalty and do not affect the quality of the products or services provided. From the perspective of Sharia Economic Law — examined through the doctrines of tas’īr (price regulation), khiyār (option to rescind), and tadlīs (fraudulent misrepresentation) — this pricing practice is legally valid (ṣaḥīḥ) because it rests on the individually informed consent of each transacting party (an-tarāḍin) and does not involve riba, gharar, or active misrepresentation of the object of sale. However, the absence of proactive disclosure of the loyalty-pricing scheme to new customers constitutes a transparency deficiency that renders the practice ethically imperfect (makrūh tanzīhī) rather than fully ideal, without invalidating the underlying contracts. The study proposes four criteria for evaluating the Sharia compliance of loyalty pricing in small-business practice and recommends that ELLY'S Cake Store adopt open disclosure of its special pricing policy to fully realize the principles of justice (al-’adl) and transparency in commercial transactions. Keywords: Sharia Economic Law; Pricing; Loyalty Pricing; Tas’īr; Transparency.